How do we develop and implement a preoperative anemia clinic designed to improve perioperative outcomes and reduce cost?. Issue 2 (23rd November 2015) - Guinn, Nicole R.; Guercio, Jason R.; Hopkins, Thomas J.; Grimsley, Aime; Kurian, Dinesh J.; Jimenez, Maria I.; Bolognesi, Michael P; Schroeder, Rebecca; Aronson, Solomon; ,
Abstract : Treatment of anemia is one of the four pillars of patient blood management programs. Preoperative anemia is common and associated with increased perioperative morbidity after surgery and increased rates of blood transfusion. Effective treatment of preoperative anemia, however, requires advanced screening, diagnosis, and initiation of therapy weeks before elective surgery. Here we describe the development and implementation of a preoperative anemia screening and treatment program at Duke University Hospital.